Antimicrobial Nanocomposite Materials Based Starch and Silver Nanoparticles - Ina Ristian (Al-Kimia, 2019)
Starchs are matrix polimer with stabilization function for nanocomposite. The present study was to investigate antimicrobial activity of nanocomposite material from metal nanoparticles such as silver and matrix polimer. Silver nanoparticles (AgNPs) were succesfully synthesized by chemical reduction silver ion with  trisodium citrate as reducing agent. AgNPs were Characterized by spectrofotometre UV-Vis and transmission electron microscope (TEM). Stability of nanocomposite starch/AgNPs was analized by differential scanning calorimetry (DSC). Nanocomposite starch and AgNPs (starch/AgNPs) were prepared by simple mixing with in-situ blending. Characterization of AgNPs using TEM shows that the synthesized particles have a size less than 50 nm. Starch/AgNPs nanocomposite has proven to reduce bacteria e. Coli is up to 98% and has good thermal stability. Antimicrobial nanocomposites based natural polimer are new potential materials for biomedical.